PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN VIDEO ANIMASI TERHADAP MINAT BELAJAR IPAS DI KELAS 4 - Lutfiah, Muthie; Darwin Effendi; Noviati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of using interactive learning media assisted by animated videos on interest in learning science and science in class 4. This research uses a quantitative approach with an experimental research type and uses Pretest - Posttest Control Group Design. The sampling technique used in this research was purposive sampling. The independent variable in this research is an animated video while the dependent variable is students' interest in learning. The population in this study was all 176 grade 4 students at SD 81 Paelmbang, while the sample was class 4A and 4B with a total of 59 students. The research data was obtained by giving a questionnaire to students' interest in learning. The data analysis technique is the t-test. Based on the results of the analysis, a significant value (2-tailed) was obtained of 0.000. Because the significant value is 0.000 < 0.05 and the resulting value is tcount = 4.547 where ttable = 1.672 with df = N-2 where N= 59 (number of samples). So it can be concluded that tcount is 4547 where ttable = 1.672, so based on testing the hypothesis H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of the use of interactive learning media assisted by animated videos on interest in learning science in class 4.